Long noncoding RNA ANRIL promotes the malignant progression of cholangiocarcinoma by epigenetically repressing ERRFI1 expression. Issue 7 (30th May 2020) - Yu, Yang; Chen, Qiaoyu; Zhang, Xunlei; Yang, Jian; Lin, Kaibo; Ji, Congfei; Xu, Aibing; Yang, Lei; Miao, Lin
Abstract: Long noncoding RNAs (lncRNAs) have recently been verified to have significant regulatory functions in many types of human cancers. The lncRNA ANRIL is transcribed from the INK4b‐ARF‐INK4a gene cluster in the opposite direction. Whether ANRIL can act as an oncogenic molecule in cholangiocarcinoma (CCA) remains unknown. Our data show that ANRIL knockdown greatly inhibited CCA cell proliferation and migration in vitro and in vivo. According to the results of RNA sequencing analysis, ANRIL knockdown dramatically altered target genes associated with the cell cycle, cell proliferation, and apoptosis. By binding to a component of the epigenetic modification complex enhancer of zeste homolog 2 (EZH2), ANRIL could maintain lysine residue 27 of histone 3 (H3K27me3) levels in the promoter of ERBB receptor feedback inhibitor 1 ( ERRFI1 ), which is a tumor suppressor gene in CCA. In this way, ERRFI1 expression was suppressed in CCA cells. These data verified the key role of the epigenetic regulation of ANRIL in CCA oncogenesis and indicate its potential as a target for CCA intervention. Abstract : ANRIL can adjust the proliferation and migration of cholangiocarcinoma (CCA) cells in vitro. Mechanistic investigations indicated that ANRIL could inhibit the expression of ERRFI1 by directly binding to EZH2, which mediated H3K27me3 in the promoter region of ERRFI1, thus accelerating CCA tumorigenesis.